Sialoglycoconjugate content of milk replacers for neonatal calves - Martín-Sosa, S.; Alonso, J.M.; Alonso, J.M.; Sánchez-Juanes, F.; Zancada, L.; García-Pardo, L.A.; Hueso, P. (Spanish Journal of Agricultural Research, 2009)
Sialoglycoconjugate contents of several milk replacers (MR) currently used in Spain have been determined. The ingestion of these compounds by calves fed bovine milk or MR is also discussed. Total sialic acids and glycoprotein-, oligosaccharide-, casein-, and lipid-bound sialic acids and free sialic acid were determined. High sialic acid contents in all the fractions studied, including total sialic acids, were found. N-acetylneuraminic acid was found to be the major sialic acid in MR. However, MR-D and H had a high N-glycolylneuraminic acid (NeuGc) content in all fractions (15-40%), while E and F only had a high NeuGc content in the glycoprotein fraction. Five different sialyloligosaccharides -3’-sialyllactose, 6’-sialyllactose, 3’-sialyllactosamine, 6’-sialyllactosamine, and disialyllactose, which are themost abundant oligosaccharides in bovinemilk- were detected in the MR. Samples B to I contained high amounts of these oligosaccharides. The content of individual gangliosides was very similar to that of bovine milk, with GD3 as the major ganglioside. Although MR are not formulated as regards their sialic acid content, high amounts of sialic acid-containing glycoconjugates with high levels of NeuGc, a sialic acid critical in the adhesion of some Escherichia coli strains to calf intestinal epitheliumwere detected. The ingestion of MR analyzed in this work could protect newborn calves from several enteric pathogens.